2016
DOI: 10.1128/aem.02281-16
|View full text |Cite
|
Sign up to set email alerts
|

Essential Genes forIn VitroGrowth of the Endophyte Herbaspirillum seropedicae SmR1 as Revealed by Transposon Insertion Site Sequencing

Abstract: The interior of plants contains microorganisms (referred to as endophytes) that are distinct from those present at the root surface or in the surrounding soil. Herbaspirillum seropedicae strain SmR1, belonging to the betaproteobacteria, is an endophyte that colonizes crops, including rice, maize, sugarcane, and sorghum. Different approaches have revealed genes and pathways regulated during the interactions of H. seropedicae with its plant hosts. However, functional genomic analysis of transposon (Tn) mutants h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 45 publications
3
14
0
Order By: Relevance
“…Another essential ncRNA was rnpB which is a component RNA of the ribonuclease P enzyme (RNase P) together with the RnpA protein (also identified as an essential gene in our study) functions in the processing of 4.5S RNA and tRNA precursor molecules in E. coli ( https://ecocyc.org/gene?orgid=ECOLI&id=EG30069 ). Similar to our findings, in a recent study, Rosconi et al (2016) found 22 tRNA genes and one 23S ribosomal RNA gene to be essential in Herbaspirillum seropedicae , an endophyte that colonizes crops like rice and maize, during in vitro growth in TY medium [ 38 ].…”
Section: Resultssupporting
confidence: 92%
“…Another essential ncRNA was rnpB which is a component RNA of the ribonuclease P enzyme (RNase P) together with the RnpA protein (also identified as an essential gene in our study) functions in the processing of 4.5S RNA and tRNA precursor molecules in E. coli ( https://ecocyc.org/gene?orgid=ECOLI&id=EG30069 ). Similar to our findings, in a recent study, Rosconi et al (2016) found 22 tRNA genes and one 23S ribosomal RNA gene to be essential in Herbaspirillum seropedicae , an endophyte that colonizes crops like rice and maize, during in vitro growth in TY medium [ 38 ].…”
Section: Resultssupporting
confidence: 92%
“…Seven bands with differential expression intensities were selected for identification by peptide mapping in a MALDI-TOF mass spectrometer ( Figure 3 ). Three bands that migrate very close in the low iron availability environment were analyzed as a single sample in the MALDI-TOF, and are collectively referred to as band E. As a control we included one band with similar intensity in both conditions, which was named band A and was shown to be the product of the gene Hsero_4295, an outer membrane porin identified recently as a candidate essential gene of H. seropedicae ( Rosconi et al, 2016 ). Band B, highly expressed in iron sufficient condition, was identified as the product of Hsero_2973, a homolog of sdhA , encoding the succinate dehydrogenase flavoprotein subunit that contains a Fe-S cluster ( McNeil et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Beneficial bacteria need to not only cope with a range of environments and climatic conditions, but actively enhance plant growth under such conditions. In addition to colonizing the crop host, the bacteria need to compete with existing soil microbiota for resources and be safe for the environment (Rosconi et al, 2016). The bacterial inoculum may be applied in conjunction with chemical pesticides and fertilizers, so it is advantageous if it is able to survive and maintain plant growth promoting activity in the presence of these additions and must also be able to survive packaging, transport and storage before it is applied to a crop (Glick, 2015;Backer et al, 2018).…”
Section: Boosting Crop Yields Via Application Of Beneficial Bacteriamentioning
confidence: 99%